English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2n^1/3 (n^2/3 + n^ -1/3)


The 1st letter n has an exponent of 1/3
The 2nd letter n has an exponent of 2/3
The 3rd letter n has an exponent of -1/3

2007-01-15 15:44:13 · 7 answers · asked by Anonymous in Science & Mathematics Mathematics

7 answers

2n+2
...or....
2(n+1)

whichever you prefer
__________________________________________________-

2n^1/3 (n^2/3 + n^ -1/3) =
2n^(1/3+2/3) + 2n^(-1/3+1/3) =
2n^(1) + 2n^(0) =
2n+2 or 2(n+1)

2007-01-15 15:48:16 · answer #1 · answered by Anonymous · 0 0

You need to use the following law of indices: a^p * a^q = a^(p+q)

So multiplying out the brackets we get:

2n^(1/3 + 2/3) + 2n^(1/3 - 1/3)
= 2n^1 + 2n^0
= 2n + 2 (since n^0 = 1)

So the final answer is 2n+2 or 2(n+1) if you prefer.

2007-01-15 23:51:23 · answer #2 · answered by martina_ie 3 · 0 0

Well, do the distribution and you get:

2n^(1/3)n^(2/3) + 2n^(1/3)n^(-1/3)

Then follow the rule about adding exponents to multiply, and you get

2n^1 + 2n^0 = 2n + 2

2007-01-15 23:50:58 · answer #3 · answered by Anonymous · 0 0

2n^1/3 (n^2/3 + n^ -1/3)
=2n+2n^0
=2n+2
=2(n+1)

2007-01-15 23:48:22 · answer #4 · answered by A 150 Days Of Flood 4 · 0 0

2n^1/3 (n^2/3 + n^ -1/3)
= 2n^(1/3 +2/3) + 2n^(1/2-1/3)
= 2n^1 + 2n ^0
=2n+2
=2(n+1)

2007-01-15 23:51:45 · answer #5 · answered by ironduke8159 7 · 0 0

2n^1/3 (n^2/3 + n^ -1/3)
= (2n^1/3)(n^2/3) + (2n^1/3)(n^ -1/3)
= 2n^(1/3+2/3) + 2n^(1/3-1/3)
=2n^1 + 2n^0
=2n + 2

2007-01-15 23:48:56 · answer #6 · answered by Roxanne 3 · 0 0

After you get your final grade, look back on how you were spoon fed, and ask yourself, "Gee, why did I get such a lousy grade?"

2007-01-15 23:53:11 · answer #7 · answered by Joe L 1 · 0 0

fedest.com, questions and answers